2017
DOI: 10.4081/aiua.2017.1.55
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison between transrectal and transperineal prostate biopsy in the detection of prostate cancer

Abstract: Background: The aim of this study was to analyze the differences between TRUSguided transrectal prostate biopsy (TR) and transperineal prostate biopsy (TP) in the diagnosis of prostate cancer. The two biopsy methods were evaluated in terms of diagnostic sensitivity and of early and late complications. Methods: This retrospective study was realized through the review of clinical records of 219 men that received a prostate biopsy between 2004 and 2014. The biopsy was performed because of elevated prostate-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The two most commonly used methods of prostate biopsy are trans‐rectal ultrasound (TRUS)‐guided biopsy and transperineal (TP) mapping biopsy, with the latter providing higher cancer detection rates [5]. MRI/MRI‐fusion guided methods are also increasingly being utilised, with even higher detection rates for clinically significant PCa [6].…”
Section: Introductionmentioning
confidence: 99%
“…The two most commonly used methods of prostate biopsy are trans‐rectal ultrasound (TRUS)‐guided biopsy and transperineal (TP) mapping biopsy, with the latter providing higher cancer detection rates [5]. MRI/MRI‐fusion guided methods are also increasingly being utilised, with even higher detection rates for clinically significant PCa [6].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst NICE guidance acknowledges the different biopsy techniques available, data on the outcomes of TRUS diagnostic biopsy are more widely available and so remain the recommended diagnostic biopsy method [12]. However, determining the most beneficial biopsy [20,21], though the recent meta-analysis by Xiang et al found that both methods had similar diagnostic efficacy but that TP biopsy was associated with a significant decrease in infection and rectal bleeding [22]. Historically, TP biopsy required the use of general anaesthetic and extensive histological analysis, however researchers at GSTT have recently investigated the outcomes of the Precision-Point™ access system (Perineologic, Cumberland, MD, USA) for freehand TP biopsies which are less resource intensive than conventional TP biopsies as they can be carried out under local anaesthetic [22].…”
Section: Utility and Discussionmentioning
confidence: 99%
“…As regards TP prostate biopsy advantage is represented by low complications rate whereas main disadvantages are necessity of anesthesia and complexity of execution; however, today refi nement of brachytherapy techniques have made it more close relationship with this prostate biopsy approach. 17 This project was funded by: Chengde science and technology and development project(N0:20142072)…”
Section: Discussionmentioning
confidence: 99%